Sustaining indigenous songs : contemporary Warlpiri ceremonial life in Central Australia - Curran, Georgia (Berghahn, 2020)
"As an ethnography of Central Australian singing traditions and ceremonial contexts, this book asks questions about the vitality of the cultural knowledge and practices highly valued by Warlpiri people and fundamental to their cultural heritage. Set against a discussion of the contemporary vitality of Aboriginal musical traditions in Australia and embedded in the historical background of this region, the book lays out the features of Warlpiri songs and ceremonies, and centers on a focal case study of the Warlpiri Kurdiji ceremony to illustrate the modes in which core cultural themes are being passed on through song to future generations"--